Increasing Students' Interest in Reading Through Picture Story Media in Play Group Harapan District, Mandor District, Landak Regency, Indonesia - Rindi, Benedikta Dita (Journal of Teaching and Education, 2024)
This research aims: 1). To increase students' interest in reading through the media of Picture Stories at KB Harapan, Mandor District, Landak Regency. 2). To determine the use of picture story media in increasing children's interest in reading at KB Harapan, Mandor District, Landak Regency. Based on the research results, the media of illustrated stories can increase students' interest in reading in group B KB Harapan, Mandor District, Landak Regency. It was indicated by the increase in children's interest in reading and learning activities using picture story media in group B KB Harapan, Mandor District, Landak Regency. The use of picture story media can increase students' interest in reading. It was shown by the increase in the percentage of children's interest in reading from pre-cycle to cycle II, which has experienced an excellent increase. In the pre-cycle initial conditions, the good category received a total percentage of 52.38%, and in the first cycle, it was 71.42%, which was the total percentage of the good category. In the second cycle, 85.71% of the students were in the excellent category and had succeeded in achieving the target the author wanted, so using picture story media can increase students' interest in reading.